2022
DOI: 10.1021/acs.joc.2c02192
|View full text |Cite
|
Sign up to set email alerts
|

[3 + 2]-Cycloadditions with Porphyrin β,β′-Bonds: Theoretical Basis of the Counterintuitive meso-Aryl Group Influence on the Rates of Reaction

Abstract: Removal of a β,β′-bond from meso-tetraarylporphyrin using [3 + 2]cycloadditions generates meso-tetraarylhydroporphyrins. Literature evidence indicates that meso-tetraphenylporphyrins react more sluggishly with 1,3-dipoles such as ylides and OsO 4 (in the presence of pyridine) than meso-tetrakis-(pentafluorophenyl)porphyrin. The trend is counterintuitive for the reaction with OsO 4 , as this formal oxidation reaction is expected to proceed more readily with more electron-rich substrates. This work presents a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 84 publications
1
4
0
Order By: Relevance
“…The OsO 4 -mediated dihydroxylation of meso-tetrahexylporphyrin 7 took place under standard conditions that are also applicable to octaalkylporphyrins and mesotetraphenylporphyrin: 1-2 equiv OsO 4 in CHCl 3 /pyridine (optionally applied in two aliquots) over several days at ambient temperature, followed by the reductive cleavage of the initially formed osmate ester (Scheme 2). We found that the osmylation takes place at a comparable, or possibly slightly lower rate, as in meso-tetraphenylporphyrin, a finding in line with our expectations for the electron-rich porphyrin 7 [26].…”
Section: The Osmylation Of Meso-tetrahexylporphyrinsupporting
confidence: 91%
See 2 more Smart Citations
“…The OsO 4 -mediated dihydroxylation of meso-tetrahexylporphyrin 7 took place under standard conditions that are also applicable to octaalkylporphyrins and mesotetraphenylporphyrin: 1-2 equiv OsO 4 in CHCl 3 /pyridine (optionally applied in two aliquots) over several days at ambient temperature, followed by the reductive cleavage of the initially formed osmate ester (Scheme 2). We found that the osmylation takes place at a comparable, or possibly slightly lower rate, as in meso-tetraphenylporphyrin, a finding in line with our expectations for the electron-rich porphyrin 7 [26].…”
Section: The Osmylation Of Meso-tetrahexylporphyrinsupporting
confidence: 91%
“…This versatile method is suitable for converting β-alkylporphyrins 1 or meso-arylporphyrins 3 to their corresponding 7,8-dihydroxychlorins 2 and 4, respectively (Scheme 1) [18][19][20][21][22][23][24]. The regiochemistry and other mechanistic aspects of this reaction are well understood [25,26]. Importantly, the diol functionality in the dihydroxychlorins can be used as a synthetic Curiously, the chemistry of meso-alkylporphyrins (5) (Figure 1), although known for decades [31][32][33], has been far less studied, by a wide margin, compared to that of their βalkyl-or meso-aryl analogues [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, the calculated HOMO−LUMO data for the osmylation reaction do not support this assumption (see Table S6). 43 In this paper, we explore various factors that can influence the activation energies and derive a scheme that can nicely rationalize all of the experimental observations by Sharpless.…”
Section: Introductionmentioning
confidence: 94%
“…As the basicity of the amine-type ligand decreases, the position of the minimum points (see the black circled points in the purple, gray, green, and orange plots in Figure A) of four curved Hammett plots accelerated by amine-type ligands shifts to the right, indicating a more electron-withdrawing styrene. The general observation that the β,β′-double bond of meso -tetrakis(pentafluorophenyl)porphyrin (T F PP) is more reactive than the corresponding bond(s) in meso -tetraphenylporphyrin (TPP) appears to have the same underlying cause. …”
Section: Introductionmentioning
confidence: 99%